Analisis Kesulitan Belajar Siswa Pada Pembelajaran Matematika Materi Pecahan Dilihat dari Kemampuan Menyelesaikan Pemecahan Masalah Matematika Kelas IV SD Negeri 2 Tlogotunggal Kabupaten Rembang - Ripit Apriliana; Ervina Eka Subekti; M. Yusuf Setia Wardana (Universitas PGRI Adi Buana Surabaya, 2021)
The purpose of this study was to determine the learning difficulties of students and to describe the factors that affect the learning difficulties of grade IV students of SD Negeri 2 Tlogotunggal Regency of Rembang as seen from their ability to solve mathematical problem solving in fraction material. The research method used in this research is qualitative with a descriptive approach. The subjects of this study were the fourth grade students of SD Negeri 2 Tlogotunggal, Rembang, totaling 25 students. Data collection techniques in this study used observation, questions, questionnaires, interviews and documentation. The results of this study indicate that students have learning difficulties in solving math problems with fractions (a) Understanding the problem by 30%, planning problem solving as much as 55.2%, implementing problem solving plans as much as 58%, and checking back as much as 83.6%. (b) Factors that affect learning difficulties in math problem solving abilities are the aspects of the family environment and aspects of the school environment.